A methodology to evaluate the maintainability of enterprise application integration frameworks. (2015) - Frantz, Rafael Z.; Corchuelo, Rafael; Roos-Frantz, Fabricia
Consulting companies that specialise in enterprise application integration commonly require adapting existing frameworks to specific domains. Currently, there are many such frameworks available, most of which provide a materialisation of the well-known catalogue of patterns that was devised by Hohpe and Woolf (2003). The decision regarding which framework must be used is critical since adaptation costs are not negligible. In this article, we report on a methodology that helps practitioners make a decision regarding which framework should be selected. To the best of our knowledge, there is not a previous methodology in the literature. Its salient features are that we have assembled a catalogue of measures regarding which there is a consensus in the literature that they are clearly aligned with the effort required to maintain a piece of software and we propose a statistically-sound method to produce a rank. We illustrate our proposal with an industrial case study that we have performed using five open-source frameworks.